EDUCAÇÃO HÍBRIDA: A BIMODALIDADE DO ENSINO DE GRADUAÇÃO EM UM CURSO DE LICENCIATURA PRESENCIAL - Gonzatto, Ana Paula (2017)
The Master’s dissertation entitled "Hybrid Education: The bimodality of undergraduate education in a degree course" has proposed to analyze bimodal education and its possibilities for mediation between the applicability of 20% on the subject of New Technologies Applied to Education in a degree course of initial teacher training. For this purpose, it was questioned: the use of educational technologies in the applicability process of Ordinance No.1.134/2016, which allows 20% of online workload in a subject of a degree course which enables autonomy and meaningful learning for the students? In this way, the overall objective was to analyze the online pedagogical practices performed in the subject, it is important to check the usability and viability of bimodal teaching in degree courses, as support for the teaching and learning process. Therefore, the research was subsidized by the law of Guidelines and Bases of education, no. 9,394/1996, as well as the Ordinance No. 1,134/2016 (Ordinance of 20%), which assisted in the distance modality approach, your historical trajectory and discussions involving the teaching and learning process, as well as the use of educational technologies in degree courses with the 20% of online workload. The study was based on the following authors: Alves (1998, 2009), Belloni (2001), Castells (1999), Canclini (2000), Fiorentini (2003), Ant (2015), Gadotti (2005), Jenkins (2009), Kenski (2007, 2008, 2012), Levy (1993), Market (2016), Moran (2001), Santinello (2006, 2009), Saviani (2008). The guidelines for the studies were: bibliographical and field research, using data collection instruments, which are: questionnaires, notes in logbooks during the lessons of New Technologies Applied to Education, which helped in the qualitative analysis of information, based on the mediation categories, collaborative learning and content. It can be noted that the above-mentioned Ordinance provides flexibility of the schedules as the student's availability, as well as bimodal education encourages the autonomy and the dynamic in the teaching learning process, demonstrating the incentive of the academic for scientific research that improves significantly the teaching quality.